Composite scaffolds of black phosphorus nanosheets and gelatin with controlled pore structures for photothermal cancer therapy and adipose tissue engineering. (August 2021) - Sutrisno, Linawati; Chen, Huajian; Chen, Yazhou; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Breast cancer treatment needs to eradicate cancer cells and restore breast defects after surgical intervention. Herein, bifunctional composite scaffolds of black phosphorus nanosheets (BPNSs) and gelatin were designed to kill breast cancer cells and induce adipose tissue reconstruction. The composite scaffolds were prepared by hybridizing photothermal BPNSs with porous gelatin matrices by adding pre-prepared ice particles to precisely adjust their pore structures. The composite scaffolds had large, well-interconnected spherical pores, which allowed cell migration and infiltration. Hybridization with BPNSs increased the compression strength of the scaffolds. The composite scaffolds possessed a high photothermal conversion capacity that was dependent on the amount of BPNSs. The composite scaffold with a high amount of BPNSs could completely kill breast cancer cells in vitro and in vivo under laser irradiation. Moreover, cell culture and animal experiment results showed that the composite scaffolds promoted lipid oil droplet formation and upregulated the expression of adipogenesis-related genes when hMSCs were cultured in the scaffolds. The composite scaffolds could offer a facile platform to exert anticancer effects against breast cancer cells and promote the reconstruction of adipose tissue. Graphical abstract: Image 1 Highlights: Composite scaffolds of black phosphorus nanosheets and gelatin were prepared. The composite scaffolds had interconnected pores and high mechanical strength. The composite scaffolds had excellent photothermal conversion capacity. The composite scaffolds could kill cancer cells under NIR laser exposure. The composite scaffolds could promote the adipogenic differentiation of hMSCs.